Male-female differences in the number of reported incident dengue fever cases in six Asian countries - Anker, Martha; Arima, Yuzo (Western Pacific Surveillance and Response, 2013)
Introduction. Demographic factors, such as age and sex, are associated with the likelihood of exposure to ,em>Aedes aegypti, the vector for dengue. However, dengue date disaggregated by both sex and ageare not routinely reported or analyzed by national surveillance systems. This study analysed the reported number of incident dengue cases by age and sex for six countries in Asia. Methods. Data for the Lao People’s Democratic Republic, the Philippines, Singapore and Sri Lanka were obtained from DengueNet; the number of male and female dengue cases was available for four age groups (< 1, 1–4, 5–14 and > 15 years) over a cumulative period of six to 10 years. Data for Cambodia (2010) and Malaysia (1997–2008) were obtained from their respective ministries of health. Results. An excess of males was found among reported dengue cases > 15 years of age. This pattern was observed consistently over several years across six culturally and economically diverse countries. Discussion. These data indicated the importance of reporting data stratified by both sex and age since collapsing the data over all ages would have masked some of the observed differences. In order to target preventive measures appropriately, assessment of gender by age is important for dengue because biological or gender-related factors can change over the human lifespan and gender-related factors may differ across countries.